Strategies against the pruritus and its consequences in atopic dermatitis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2018)
Atopic dermatitis is one of the most pruriginous disorders of childhood. This is why the pruritus is often the first symptom reported by the family and this is often considered by the family a matter apart from the disease. Strategies against the pruritus start from the most objective as possible evaluation of the severity of itching, age of the patient, whole severity of atopic dermatitis, distribution of the lesions and their local severity. Particularly, the evaluation of the severity of the pruritus is based on the number of pruriginous crises in a day, on the loss of sleep and on the severity of scratch marks. According to these criteria, three varieties of atopic dermatitis can be isolated as follows: 1- mild, not itchy atopic dermatitis, 2- scarcely itchy atopic dermatitis with family overevaluation of the pruritus and 3- atopic dermatitis with severe pruritus. Even from a therapeutical point of view five subvarieties can be isolated in the third variety as follows: 3a pruritus sine dermatitis, 3b localized exudative dermatitis, 3c localized, lichenified atopic dermatitis, 3d early generalized atopic dermatitis of the first year and finally 3e late generalized atopic dermatitis.